INTERNATIONAL FINANCIAL RESOURCES AND INCOME INEQUALITY IN INDONESIA - Sapriyadi Ansar; Nurhuda Nurhuda; Muhammad Syukri; Charisma Ekawaty (JEMMA (Journal of Economic, Management and Accounting), 2024)
The question is whether these international financial sources have really flowed a lot in developed countries where the rate of return on capital is much greater and of course the investment risk is minimal compared to developing countries? This is what underlies the need for analysis to find out more about what and how big the impact of international financial sources is on development in Indonesia.  This research uses time series data for the last 17 years (2004-2020) which comes from online World Bank publications accessed on the official website. The technical analysis used in this research is structural model analysis. This research aims to determine the impact of remittances, FDI and foreign loans on income inequality through economic growth in Indonesia. The variables Remittances, FDI and foreign loans are independent variables and income inequality is the dependent variable while economic growth is the intervening variable in this research.  Remittances have a significant positive effect on income inequality through economic growth, FDI has no significant effect on income inequality through economic growth, and the foreign loan variable has a significant negative effect on income inequality through economic growth.